Two new species of Rhagophthalmus Motschulsky (Coleoptera: Rhagophthalmidae) from Matzu Archipelago, Taiwan with biological commentary - Ho, Jen-Zon; Chen, Young-Fa; Cheng, Su-Han; Tsai, Xi-Lian; Yang, Ping-Shin (Zootaxa, 2012)
Two new species of Rhagophthalmus Motschulsky, R. beigansis Ho sp. nov. and R. giallolateralus Ho sp. nov. collected in a vulnerable environment in two small islets of Matzu Archipelago, Lienchiang County are described and illustrated. This brings the total number of species in this genus to 35, and the number known from small off shore islets and islands to 10. Their importance to the conservation of such small and fragile island habitats is discussed.